2005
DOI: 10.1021/mp0500418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Subcellular Localization of Progesterone Receptor on Import Kinetics and Transcriptional Activity

Abstract: Progesterone receptors (PR) are ligand-activated transcription factors that modulate transcription by activating genes. There are two isoforms of PR, PRA and PRB. In most cell contexts, the PRA isoform is a repressor of the PRB isoform. Without hormone induction, PRA is mostly located in the nucleus whereas PRB distributes both in the nucleus and in the cytoplasm. In this paper, a new model system has been used to study the impact of initial subcellular localization, and import rate of progesterone receptor on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Interestingly, the nuclear translocation rate of GR in that NL1-deleted mutant is identical to the rate shown in cells where the hsp90·FKBP52·motor protein complex is disrupted. A similar observation has also been reported for a PR mutant where the active NLS is absent 64. As expected, this PR mutant is cytoplasmic in a medium without steroid.…”
Section: Transport Across Nuclear Poressupporting
confidence: 88%
“…Interestingly, the nuclear translocation rate of GR in that NL1-deleted mutant is identical to the rate shown in cells where the hsp90·FKBP52·motor protein complex is disrupted. A similar observation has also been reported for a PR mutant where the active NLS is absent 64. As expected, this PR mutant is cytoplasmic in a medium without steroid.…”
Section: Transport Across Nuclear Poressupporting
confidence: 88%
“…In addition to both PRA/B transcriptional start sites, a single nucleotide polymorphism (SNP) called PR?331G/A creates a new TATA element, which results in additional PRB transcription [58]. Using transiently transfected PR constructs, PRA expression leads mainly to gene repression, whereas PRB correlated with gene activation [59,60]. A comparison of both isoforms showed that PRA was Nterminally truncated by 165 amino acid residues resulting in a protein size of 94 kDa compared to PRB with 116 kDa (Fig.…”
Section: Estrogen and Progesterone Isoformsmentioning
confidence: 99%
“…3) [61]. In addition, PRA is mostly located in the nucleus, whereas PRB distributes between the nucleus and cytoplasm [59]. PRA and PRB are co-expressed in many cell types where they appear to be synthesized in equal proportions.…”
Section: Estrogen and Progesterone Isoformsmentioning
confidence: 99%
“…In most cell contexts, the PRA isoform is a repressor of the shorter PRB isoform, and without hormone induction it is mostly located in the nucleus, whereas PRB distributes both in the nucleus and in the cytoplasm. PRB accumulates in the nucleus after progesterone binding, a process that directly correlates with PR mediated transcription [Li et al, 2005; Lim et al, 1999]. …”
Section: Nuclear Translocationmentioning
confidence: 99%